1992
DOI: 10.1007/bf02072224
|View full text |Cite
|
Sign up to set email alerts
|

Development of height and weight in children with diabetes mellitus: Report on two prospective multicentre studies, one cross-sectional, one longitudinal

Abstract: Optimal regimen for insulin therapy should lead to normal longitudinal growth and weight gain in children with diabetes mellitus. However, reports published so far indicate that this goal of paediatric diabetology is currently not achieved in a considerable number of patients. In a cross-sectional sample of 89 children with insulin dependent diabetes mellitus (IDDM) for more than 3 years, we found the relation of height to weight to be significantly different compared to 102 healthy school children of similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
34
1
8

Year Published

1994
1994
2006
2006

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 28 publications
7
34
1
8
Order By: Relevance
“…Similar data have been reported by other authors (62). It has also been shown that height at diagnosis in a group of 89 children with duration of diabetes of more than 3 years and a mean age of 8.9^2.2 years was not different compared with 102 healthy control children (63). In a longitudinal study, it has been shown that height at diagnosis in a total of 436 children with diabetes was significantly above the reference population.…”
Section: Growth and Developmentsupporting
confidence: 87%
“…Similar data have been reported by other authors (62). It has also been shown that height at diagnosis in a group of 89 children with duration of diabetes of more than 3 years and a mean age of 8.9^2.2 years was not different compared with 102 healthy control children (63). In a longitudinal study, it has been shown that height at diagnosis in a total of 436 children with diabetes was significantly above the reference population.…”
Section: Growth and Developmentsupporting
confidence: 87%
“…Several studies have suggested that leptin also influences sexual progression through puberty (6)(7)(8). Impaired growth and pubertal delay have been observed in children with diabetes (9)(10)(11). Also, these children tend to develop obesity, even if they are treated with modern insulin therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The question whether diabetes, well treated with conventional means, still compromises the growth of diabetic children, remains controversial. Many studies claim that longitudinal growth is impaired in diabetic children (1)(2)(3)(4)(5)(6)(7). Some investigators have observed catch-up growth in poorly controlled diabetic children after a better degree of control had been achieved (8)(9)(10).…”
mentioning
confidence: 99%